Determinants for knowledge sharing behaviours among undergraduate students in Public University in Malaysia / S. H. Saleh and A. Z. H. Samsudin. - Saleh, S. H.; Samsudin, A. Z. H. (Perpustakaan Tun Abdul Razak (PTAR), 2021)
Purpose - This study aims to investigate the factors affecting knowledge sharing behaviour (KSB) among undergraduate students in X University in Malaysia. University X was used instead of the university's name to protect the identity of the university. The objectives are: i) To identify the factors that affecting knowledge sharing behaviour among undergraduate students in Public University in Malaysia, ii) To determine relationship between self-efficacy and knowledge sharing behaviour, iii) To determine relationship between trust and knowledge sharing behaviour, iv) To determine relationship between technology availability and knowledge sharing behaviour and v) To determine relationship between perceived usefulness of technology and knowledge sharing behaviour. Design/methodology/approach - The data from 297 students out of 1,486 undergraduate students in a X University in Malaysia has been collected. Data from 297 students were completed and the demographic shows 197 females (66.3%) and 38 males (33.7%). The quantitative approach and questionnaire instrument are the research methodology and technique used to investigate this phenomenon. Data analysis conducted using SPSS software to constructs the finding results. Findings - The results indicated the highest correlation value is between trust and knowledge sharing behavior which comply with one of the objective to determine relationship between trust and knowledge sharing behaviour, whereas the lowest correlation value is between technology availability and knowledge sharing behavior which comply with one of the objective to determine relationship between technology availability and knowledge sharing behaviour. Therefore, it could be considered that the variables used in this study have positive correlation either moderate or low relationship. Research limitations/implications - There are several limitations of this study. Firstly, this study was only focused on undergraduate students from one Public University in east coast peninsular. Therefore, it may not be generalised to other Public University across Malaysia. Secondly, we did not relate the students' knowledge sharing to academic performance, which may be of interest to be looked into in future studies. Moreover, by utilizing a single method, i.e. quantitative, we may not be able to assess and understand student's intention of knowledge sharing in depth, as most behavioral studies consisted of mixed method approach. Lastly, it is the nature of a cross sectional survey study which limits our analysis. It would be of much benefit if we can perform a prospective study in assessing the changes in students' knowledge sharing behaviour as they progress in the subsequent years of their studies. Conclusion - The conclusion could be drawn that knowledge sharing was found to be significantly related to all components under study i.e. self-efficacy, trust, technological availability, and perceived usefulness of technology. Personal attitudes and technological factors may act as determinants of knowledge sharing among university undergraduate students in X University in Malaysia.